Environmental management competitive pressure effect on SME environmental innovation activities: A green supply chain perspective - Rashid, A. A.; Sidek, Atiah Abdullah; Suffian, S. A.; Che Daud, Mohd Radzi (Institute of Physics Publishing, 2018)
The idea of assimilating green supply chain is to integrate and establish environmental management into the supply chain practices. The study aims to explore how environmental management competitive pressure influences a SME company in Malaysia to incorporate green supply chain integration, which is an efficient platform to develop environmental innovation. This study further advances green supply chain management research in Malaysia by using the method of quantitative analysis to analyze the model developed which data will be collected based on a sample of SMEs in Malaysia in manufacturing sector. The model developed in this study illustrates how environmental management competitive pressure from main competitors affects three fundamental dimensions of green supply chain integration. The research findings suggest that environmental management competitive pressure is a vital driving force for a SME company to incorporate internal and external collaboration in developing green product innovation. From the analysis conducted, the study strongly demonstrated that the best way for a company to counteract competitor’s environmental management success is to first implement strong internal green product development process then move to incorporate external environmental management innovation between their suppliers and customers. The findings also show that internal integration of green product innovation fully mediates the relationship of environmental management competitive pressure and the external integration of green product innovation.